PEMAHAMAN NILAI-NILAI PAPPASANG DALAM MENINGKATKAN KARAKTER BANGSA YANG BERKEARIFAN LOKAL - Dedi Gunawan Saputra (Risenologi, 2018)
Indonesian consists of various different people, tribes, languages which is enrich byculture. As part of Indonesian, Makassar society is very proud of their languages, arts,and the culture. It can be reflected that Makassar language are still be spoken by itspeople. Makassar language is part of Indonesian that have value sublimes for itssociety. Value sublimes can be found on pappasang. Pappasang is wise words fromMakassar ancestors that contains about the rules in life, live hoods, also the rule inrelationships with with the God. Through the application of pappasang, it is expectedto form the characters and also give benefits to the society, especially to Makassar society and Indonesian in general. Besides, pappasang values can be as direction totransform the society to be better. By deep understanding about pappasang, it will makeIndonesian as opened mind country with the current globalization which is can keep ofthe ethics and morality among human so that humanity aspect and modernity will noterase the local wisdom that have already become an important fundamental of nation inestablishing the characters. The aim of this paper to describe pappasang values asmedia to develop nation characters with local wisdom. The method is descriptive byanalyzing the context of pappasang values. In pappasang, the researcher found variousvalues such as honesty, spiritual, leadership, abashment, and unity values. The values inpappasang is very high because there are pearls that adore by Makassar society.Therefore, the understanding of pappasang values are needed for Indonesian live in thepresent.